Progression of fertility-sparing treatment for atypical endometrial hyperplasia in a woman with lynch syndrome: a case report and review of the literature - Hsu, Ya-Ting; Chen, Chi-Hau (Frontiers in Oncology, 2024)
Endometrial cancer in Lynch syndrome is characterized by a higher incidence, younger age at onset, and increased recurrence rates compared to sporadic cases, while the safety and efficacy of fertility-sparing treatments remain uncertain. This case report presents the oncology outcome of fertility-preserving treatment in a 39-year-old woman diagnosed with Lynch syndrome and atypical endometrial hyperplasia. Initially, she responded favorably to fertility-preserving treatment but subsequently experienced disease relapse and rapid progression during retreatment. Final pathology revealed endometrial cancer with metastasis to the right ovary, categorized as FIGO 2023 stage IIIA1. This population's unique molecular mechanisms and genetic mutations warrant special consideration when opting for fertility-sparing treatment. We have reviewed and summarized the oncology and pregnancy outcomes among Lynch syndrome and MMR-deficient patients through previous literature. However, no studies have investigated retreatment after recurrence in Lynch syndrome. Our case highlights the potential risks associated with retreatment following relapse. Vigilant monitoring and prompt consideration of surgical intervention are recommended upon disease relapse.